Pengaruh Model Pembelajaran Scramble Terhadap Hasil Belajar IPAS di Kelas V SDN 196/II Taman Agung - Misa Anggraini; Sundahry; Dhini Mufti (Master Journal of Future Education, 2026)
This study was motivated by the low academic achievement of fifth-grade elementary school students in the subject of Science and Social Studies (IPAS). The primary aim of this research was to examine the effect of the Scramble learning model on students' learning outcomes after its implementation in the classroom. A quantitative approach was employed, using a Pre-Experimental method with a One Group Pretest-Posttest design. The research subjects consisted of all fifth-grade students at SDN 196/II Taman Agung. Data were collected through testing, and analyzed using prerequisite tests (normality test) and final data analysis through a paired sample t-test. The results of the normality test indicated that both pretest and posttest data were normally distributed, with significance values of 0.674 and 0.407, respectively. The hypothesis test using the paired sample t-test produced a significance value of 0.000 (< 0.05), indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. These findings suggest that the Scramble learning model has a significant effect on improving the IPAS learning outcomes of fifth-grade students.